1,2,4,5-Tetrafluoro-3,6-diiodobenzene-4-(pyridin-4-ylsulfanyl)pyridine (1/1) - Arman, H.D.; Kaulgud, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title 1:1 adduct, C(10)H(8)N(2)S center dot C(6)F(4)I(2), comprises a half-molecule of 1,2,4,5-tetrafluoro-3,6-diiodobenzene, and half a 4-(pyridin-4-ylsulfanyl) pyridine molecule. The former is completed by crystallographic inversion symmetry, the latter by twofold symmetry, with the S atom lying on the rotation axis. The almost planar 1,2,4,5-tetra-fluoro- 3,6-diiodobenzene molecule (r.m.s. deviation of all 12 atoms = 0.016 angstrom) and twisted 4-(pyridin-4-ylsulfanyl) pyridine molecule [dihedral angle between pyridyl rings = 54.88 (13)degrees] are connected by N center dot center dot center dot I interactions [2.838 (4) angstrom], generating a supramolecular chain with a step-ladder topology. These chains are connected in the crystal by C-H center dot center dot center dot F and C-H center dot center dot center dot pi(pyridyl) interactions.